2022
DOI: 10.3390/ijerph19031596
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Heavy Metal Contamination of Roadside Soils Alongside Buddha Nullah, Ludhiana, (Punjab) India

Abstract: The present study was carried out to determine the physico-chemical characteristics and heavy metal contents in roadside soil samples collected during 2 sampling periods (September 2018 and April 2019) from 8 different roadside sites lying parallel to the Buddha Nullah, an old rivulet, flowing through Ludhiana, (Punjab) India. The contents (mg/kg) of seven metals (cadmium, chromium, cobalt, copper, lead, nickel and zinc) were estimated using a flame atomic absorption spectrophotometer. Among the metals analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 83 publications
(92 reference statements)
3
6
0
Order By: Relevance
“…Application of magnesium fertilizers such as magnesium nitrate and magnesium sulfate could be the cause of high magnesium levels in the sites studied. Similar results were reported earlier by Kaur et al (2022) in roadside soil samples collected from the vicinity of Buddha Nullah, Ludhiana, Punjab where the contents of calcium and magnesium were found in the range of 0.12-3.13 mg/g and 0.032-0.609 mg/g. Concentration of sodium in all soil samples ranged from 0.45 mg/g (BLE) to 0.62 mg/g (AWL).…”
Section: Genotoxic Potentialsupporting
confidence: 91%
See 3 more Smart Citations
“…Application of magnesium fertilizers such as magnesium nitrate and magnesium sulfate could be the cause of high magnesium levels in the sites studied. Similar results were reported earlier by Kaur et al (2022) in roadside soil samples collected from the vicinity of Buddha Nullah, Ludhiana, Punjab where the contents of calcium and magnesium were found in the range of 0.12-3.13 mg/g and 0.032-0.609 mg/g. Concentration of sodium in all soil samples ranged from 0.45 mg/g (BLE) to 0.62 mg/g (AWL).…”
Section: Genotoxic Potentialsupporting
confidence: 91%
“…The use of water from the nearby owing polluted Bhuddha Nullah, for irrigation purposes could be responsible for the high levels of Cd in the study locations exceeding the permissible limit of 0.06 mg/kg Agarwal (2009). The ndings are comparable to those of Kaur et al (2022) where Cd content (0.03 to 0.46 mg/kg) in most of the samples were above the safe limit. Farid et al (2015) reported that Cd enters the soil through the use of phosphate fertilizers, Cd-contaminated sewage sludge and manure with phosphate fertilizers, being the primary source of Cd pollution, in agricultural soil.…”
Section: Heavy Metal Contents In Soilsupporting
confidence: 78%
See 2 more Smart Citations
“…Ye et al (2015) claimed that there was a signi cant correlation between metal concentrations including Pb in the soil texture and Lead content in the vegetables tissue [38]. Vicinity of road tra c [39], transferring of dust particles contain lead, and irrigation of farms using raw wastewater and e uents [40] could be attributed to the high concentration of Pb in the vegetables tissue [41]. The average concentration of Ni, Cu, and Zn in all samples was more than the recommended range by FAO/WHO.…”
Section: Resultsmentioning
confidence: 99%